Biologic Cost per Effectively Treated Rheumatoid Arthritis Patient in a Large Managed Care Population: A Retrospective Cohort Study - Tao Gu; Neel Shah; Gaurav Deshpande; Derek H. Tang; Debra F. Eisenberg; David J. Harrison (Journal of Health Economics and Outcomes Research)
**Background:** Until recently, the lack of clinical outcomes information for rheumatoid arthritis (RA) in administrative claims databases limited their use in comparative effectiveness research. A validated claims-based algorithm has been developed to estimate the effectiveness of biologics for RA, allowing for estimation of cost and effectiveness in the same database.